Answer: The answer is given below.
Step-by-step explanation: We are given an equality involving logarithm and we are to show the implication of L.H.S. to R.H.S.
We will be using the following two properties of logarithm:
The proof is as follows:
Hence proved.
OM=18, so OQ=QM=18/2=9.
Given QU=8
from figure OQU is a right angled triangle , so OU^2=OQ^2 + QU^2
OU^2 = 9*9 + 8*8 = 81+72=153;
OU=sqrt(153) = 12.37 =13(approx);
From given statements of congruent NT and OU will also be congruent or identical. So, NT=OU=13
Answer:
Part a) The raisins cost $0.8 per ounce
Part b) 1.25 ounces
Step-by-step explanation:
<u><em>The correct question is</em></u>
Jackson bought 5 ounces of raisins for $4 dollars.
a) How much do raisins cost per ounce?
b) How many ounces of raisins can be bought for $1?
Part a) How much do raisins cost per ounce?
we know that
To find out the unit rate divide the total cost by the total weight
so
therefore
The raisins cost $0.8 per ounce
Part b) How many ounces of raisins can be bought for $1?
we know that
The raisins cost $0.8 per ounce
using proportion
Find out how many ounces of raisins can be bought for $1
Let
x -----> the ounces of raisins
Answer:
80 adults
Step-by-step explanation:
The number of kids is $10,000/$50 = 200. The number of adults is 2/5 of that, or 80.
There are 80 adults in the group.
C. x³-4x²-16x+24.
In order to solve this problem we have to use the product of the polynomials where each monomial of the first polynomial is multiplied by all the monomials that form the second polynomial. Afterwards, the similar monomials are added or subtracted.
Multiply the polynomials (x-6)(x²+2x-4)
Multiply eac monomial of the first polynomial by all the monimials of the second polynomial:
(x)(x²)+x(2x)-(x)(4) - (6)(x²) - (6)(2x) - (6)(-4)
x³+2x²-4x -6x²-12x+24
Ordering the similar monomials:
x³+(2x²-6x²)+(-4x - 12x)+24
Getting as result:
x³-4x²-16x+24